Psychosocial risks of working in Psychosocial Care Centers for children and adolescents in the COVID-19 pandemic - Agnes Olschowsky; Fabiane Machado Pavani; Gabriella de Andrade Boska; Lara Lopes Rodrigues; Juliana Ahrends de Oliveira Maia; Maria de Lourdes Custódio Duarte (Rev Rene, 2025)
Objective: to identify the psychosocial risks faced by professionals at child and adolescent psychosocial care centers in the context of the COVID-19 pandemic. Methods: a cross-sectional quantitative study was carried out at three psychosocial care centers for children and adolescents, with a sample of 23 professionals. Data were collected using a self-completion instrument consisting of sociodemographic variables, health conditions, work characteristics, and the Protocol for the Assessment of Psychosocial Risks at Work. Descriptive statistics were analyzed. Results: psychosocial risks were classified as low, medium, and high for the Prescribed Work Organization, Management Style, and Pathogenic Suffering at Work scales. It was identified that the psychosocial risk of working in the Child and Youth Psychosocial Care Centers during the pandemic was medium for the forms of work organization, the indignity factor, and physical harm. Conclusion: the psychosocial risk in this study was classified as medium, especially in the areas of work organization, pathogenic suffering in the indignity factor, and physical harm. Contributions to practice: identification of scales to understand psychosocial risks in the Psychosocial Care Network workers and aspects relevant to constructing action plans and mental health care in the workplace.